Indirect comparison of the efficacy and safety of alirocumab and evolocumab on major cardiovascular events: a systematic review and network meta-analysis - Xu, Leyu; Lei, Ming; Li, Liren; Li, Yilei; Gu, Chunping; Zheng, Ping (Frontiers in Pharmacology, 2025)
BackgroundAlirocumab and evolocumab are proprotein convertase subtilisin/kexin type 9 inhibitors that significantly reduce the relative risk of cardiovascular events. However, the relative efficacy and safety of alirocumab and evolocumab in different patient groups still warrant further indirect comparison. This systematic review and network meta-analysis indirectly compared the efficacy and safety of alirocumab and evolocumab on major cardiovascular events.MethodsPUBMED, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials (CENTRAL) databases were comprehensively searched to extract randomized controlled trials (RCTs) regarding alirocumab and evolocumab published from inception to 17 August 2024. The meta-analysis was performed using Software Review Manager 5.4 and R 4.1.0 software.ResultsThis network meta-analysis included 26 RCTs with 64,921 patients. Among these, 13 RCTs included patients receiving alirocumab or placebo (n = 13,365) and 13 RCTs included patients receiving evolocumab or placebo (n = 22,048). Compared with the placebo, treatment with alirocumab and evolocumab significantly reduced the relative risk of major adverse cardiovascular and cerebrovascular events (MACCE), myocardial infarction, stroke, and coronary revascularization. Furthermore, alirocumab and evolocumab groups did not show significant differences in MACCE [relative risk (RR): 0.99, 95% confidence interval (CI): 0.88–1.11], cardiovascular death (RR: 0.83, 95% CI: 0.65–1.06), myocardial infarction (RR: 0.87, 95% CI: 0.74–1.03), stroke (RR: 0.96, 95% CI: 0.71–1.29), coronary revascularization (RR: 0.88, 95% CI: 0.77–1.01), and any adverse event (RR: 0.91, 95% CI: 0.76–1.09). Moreover, the all-cause mortality rates were lower for patients treated with alirocumab compared to those treated with evolocumab (RR: 0.84, 95% CI: 0.70–1.00), but the difference was not statistically significant.ConclusionAlirocumab and evolocumab demonstrated comparable efficacy in reducing the relative risk of major cardiovascular events. The all-cause mortality rates were lower in patients treated with alirocumab compared to those treated with evolocumab but the differences were not statistically significant, probably due to heterogeneity in the sample size and follow-up duration between different studies. Both drugs exhibited comparable safety profiles.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD42024505327.